Green room-temperature phosphorescent carbon dots and preparation method thereof

A one-step hydrothermal method was used to prepare green room-temperature phosphorescent carbon dots doped with nitrogen, phosphorus, and boron, which solved the problems of high cost, high toxicity, and complex preparation of traditional phosphorescent materials. It achieved a long-life dual luminescence effect and is suitable for information encryption and anti-counterfeiting materials.

CN119286511AActive Publication Date: 2025-01-10TIAN JIN GONG YE DA XUE SHAO XING KE QIAO YAN JIU YUAN
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411472057.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-10
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

Existing traditional phosphorescent materials are expensive, have complex preparation processes, are highly toxic, and have short fluorescence lifetimes, making it difficult to meet the demand for efficient, green, and environmentally friendly anti-counterfeiting materials.

Method used

A one-step hydrothermal method was used to form a network structure of carbon dots using arginine, phosphoric acid, and boric acid as raw materials. Nitrogen, phosphorus, and boron atoms were then doped to promote intersystem crossing of excitons, thus preparing green room-temperature phosphorescent carbon dots with dual luminescence properties.

Benefits of technology

The preparation process is simple and environmentally friendly, with significant dual fluorescence and phosphorescence effects and a phosphorescence lifetime of up to 12 seconds. It solves the problems of high cost, high toxicity and complex preparation of traditional materials and has excellent optical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286511A_ABST
    Figure CN119286511A_ABST
Patent Text Reader

Abstract

The invention provides green room temperature phosphorescence (RTP) carbon dots (CDs) and a preparation method thereof in the technical field of luminescent carbon materials, and solves the problems of complex preparation process, high cost and high toxicity of a traditional phosphorescent material, economical arginine, phosphoric acid and boric acid are used to prepare an RTP CDs material through a simple one-step hydrothermal method, and the RTP CDs material can be used for preparing the luminescent material under ultraviolet light. The CDs show blue fluorescence, after the ultraviolet light is removed, the macroscopic afterglow of the phosphorescent CDs is green and still lasts for about 12 seconds, and the CDs are endowed with excellent optical performance due to the compact cross-linked structure and the multi-atom co-doping effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of luminescent carbon materials, and specifically relates to green room temperature phosphorescent (RTP) carbon dots (CDs) doped with nitrogen (N), phosphorus (P) and boron (B) and a preparation method thereof. Background Art

[0002] In recent years, due to the development of science and technology, anti-counterfeiting materials cannot meet the needs of social development, and there is an urgent need to develop efficient anti-counterfeiting materials. Fluorescent materials have been studied in depth in anti-counterfeiting applications. However, similar emission characteristics can be obtained by using certain substitutes or simply mixing different fluorescent materials, thus showing poor anti-counterfeiting performance. In terms of anti-counterfeiting materials, room temperature phosphorescent (RTP) materials have always been a hot spot in anti-counterfeiting applications. After turning off the external excitation light source, RTP materials will have afterglow, while fluorescent materials will be extinguished immediately. This characteristic makes RTP materials anti-counterfeiting not easy to be imitated. RTP materials are widely used in anti-counterfeiting. The most common RTP materials are traditional rare earth metal complexes and organic compounds. However, due to the high production cost, non-renewable resources, complex preparation process and high toxicity, the development of traditional phosphorescent materials is limited. Therefore, there is an urgent need to develop optical anti-counterfeiting materials with excellent optical properties, green environmental protection, low cost and simple preparation.

[0003] As a new material, carbon dots (CDs) have developed rapidly in recent years. Due to their low production cost, low toxicity, excellent optical properties and excellent biocompatibility, CDs have attracted widespread attention and are widely used in anti-counterfeiting, optical devices, sensors and biological cell imaging. CDs are a zero-dimensional carbon nanomaterial with a spherical or core-shell structure, including carbon nanodots (CNDs), carbon quantum dots (CQDs), carbonized polymer dots (CPDs), etc. However, single fluorescent CDs are limited in anti-counterfeiting due to the fluorescence interference of the object itself, and the fluorescence lifetime is relatively short, which limits the application of CDs materials. In the patent "A sunlight-excited room temperature phosphorescent carbon dot@alumina composite material and its preparation method (application publication number CN 117903795 A)", a two-step method is used for preparation and high-temperature heating in a muffle furnace. In comparison, the present invention uses a simple one-step hydrothermal doping method of multiple atoms and the temperature used is not high, which consumes less energy and is relatively safe. Moreover, the phosphorescence lifetime of CDs in the patent "A time-responsive color-changing phosphorescent carbon dot ink and its preparation method and application (application publication number CN 112500740 A)" is less than 0.4 s, and the afterglow time is only 0.9 s, which is difficult to distinguish with the naked eye, while the phosphorescence lifetime of the present invention is 0.9 s, and the afterglow time can be as long as 12 s. Finally, the patent "A phosphorescent carbon dot-metal organic framework composite material and its preparation method and application (application publication number CN 114381261 A)" invented RTP CDs by a two-step method, and the maximum afterglow time is 9 s. The preparation method of the present invention is simple and the afterglow time of RTP CDs is relatively long, which is 12 s. In short, the preparation method of the present invention is simple, environmentally friendly, low in energy consumption and relatively safe, and has relatively excellent optical properties.

[0004] The present invention uses arginine, phosphoric acid and boric acid as raw materials, forms a network structure through intermolecular cross-linking, and carbonizes into CDs as the temperature rises. The covalent bonds and hydrogen bonds generated by the cross-linking limit the molecular vibration and rotation, stabilize the triplet excitons, reduce non-radiative transitions, and promote the intersystem crossing (ISC) of the excitons from the lowest singlet state to the lowest triplet state by co-doping N, P and B atoms, thereby promoting the generation of RTP. The RTP CDs of the present invention provide ideas for the preparation of luminescent carbon materials and show great application potential. Summary of the invention

[0005] The present invention aims to solve the problems of high cost, complicated preparation process and high toxicity of traditional phosphorescent materials, and provides a simple, low-cost, environmentally friendly and excellent luminescent green room temperature phosphorescent CDs preparation method. The method changes the amount of raw materials and the reaction temperature, selects the optimal reaction conditions, and obtains CDs materials with dual luminescence of phosphorescence and fluorescence. At the same time, the one-step hydrothermal method used in the reaction makes the whole preparation process relatively simple and environmentally friendly.

[0006] A green room temperature phosphorescent carbon dot and a preparation method thereof, comprising the following steps: Step 1: Take 1.3936 g of arginine, different volumes of phosphoric acid and 1 g of boron-containing substance, add them into a beaker containing 20 mL of solvent, and stir the solution with a magnetic stirrer until it becomes clear and transparent; Step 2: Transfer the mixed solution prepared in step 1 to a polytetrafluoroethylene high-pressure reactor, and then place it in a muffle furnace to react at high temperature for a certain period of time; Step 3: Take out the brown-yellow liquid obtained by the reaction in step 2, filter it with a 0.22 μm filter membrane to remove the carbon residue, then transfer the brown-yellow transparent solution to a glass culture dish, dry it in an oven at 180°C for 6 h, grind the final solid into powder with a mortar and collect CDs.

[0007] Further, it is characterized in that: the volume of phosphoric acid in step 1 is 525, 800, 1050 and 1315 μL.

[0008] Furthermore, the solvent in step 1 is one of water, ethanol and N,N-dimethylformamide (DMF).

[0009] Furthermore, the boron-containing substance described in step 1 is one of boric acid (H3BO3) and boron oxide (B2O3).

[0010] Furthermore, the reaction temperature described in step 2 is set to 180°C, 200°C, 220°C and 240°C.

[0011] Furthermore, the reaction time described in step 2 is set to 6 h, 8 h and 10 h.

[0012] Compared with the prior art, this method has the following advantages: (1) CDs were prepared by a one-step hydrothermal method, which is a simple and environmentally friendly process.

[0013] (2) The prepared CDs have dual luminescence effects of fluorescence and phosphorescence.

[0014] (3) The phosphorescence lifetime of CDs is long and the phosphorescence afterglow time can reach 12 s in a dark environment.

[0015] (4) It solves the problems of complex preparation process, high toxicity and high cost of traditional phosphorescent materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a TEM image and a particle size distribution diagram of CDs in Example 2 of the present invention; Figure 2is the FTIR spectrum of CDs in Example 2 of the present invention; Figure 3 is the XRD spectrum of CDs in Example 2 of the present invention; Figure 4 is a phosphorescence lifetime decay graph of CDs in Example 2 of the present invention; Figure 5 This is the luminescence of the CDs powder in Example 2 of the present invention. DETAILED DESCRIPTION

[0017] The specific implementation scheme provided by the present invention is as follows: A green room temperature phosphorescent carbon dot and a preparation method thereof, comprising the following specific steps: 1) Take 1.3936 g of arginine, (525, 800, 1050 and 1315 μL, preferably 800 μL) of phosphoric acid and 1 g of boric acid (the optimal molar ratio is 1:1.5:2), add them to a beaker containing 20 mL of ultrapure water, and stir the solution with a magnetic stirrer until it becomes clear and transparent; 2) transferring the mixed solution prepared in step 1) into a polytetrafluoroethylene high-pressure reactor, and then placing it in a muffle furnace, and heating the reaction at (180, 200, 220 and 240° C., preferably 220° C.) for 8 h; 3) The brown-yellow liquid obtained by the reaction in step 2) was taken out, filtered with a 0.22 μm filter membrane to remove carbon residue, and then the brown-yellow transparent solution was transferred to a glass petri dish, placed in an oven at 180° C. and dried for 6 h. The final solid was ground into powder with a mortar and pestle and then CDs were collected.

[0018] The morphology and dispersibility of the CDs prepared by the present invention were detected by a transmission electron microscope (TEM); the molecular structure and functional groups of the CDs were analyzed by a Fourier transform infrared spectrometer (FTIR); and the crystal structure of the CDs was analyzed by an X-ray diffractometer (XRD). In order to study the luminescent properties of the CDs, the phosphorescence intensity of different CDs was tested by a fluorescence spectrophotometer, and the room temperature phosphorescence lifetime of the CDs was tested by an FLS1000 steady-state transient fluorescence spectrometer.

[0019] To realize the above-mentioned technology, the present invention is described below in combination with the embodiments of the present invention through drawings and embodiments. However, the embodiments described in the present invention are only part, not all embodiments. The technical solutions and methods for improving the present invention all belong to the protection scope of the present invention.

[0020] The preparation process is basically the same, the only difference is that the volume of phosphoric acid in step 1) is changed.

[0021] Take 1.3936 g of arginine, different volumes of phosphoric acid and 1 g of boric acid as shown in Table 1, add them into a beaker containing 20 mL of ultrapure water, and stir the solution with a magnetic stirrer until it becomes clear and transparent; 2) The mixed solution prepared in step 1) was transferred into a polytetrafluoroethylene high-pressure reactor, and then placed in a muffle furnace and heated at 220°C for 8 h; 3) The brown-yellow liquid obtained by the reaction in step 2) was taken out, filtered with a 0.22 μm filter membrane to remove carbon residue, and then the brown-yellow transparent solution was transferred to a glass petri dish, placed in an oven at 180°C for 6 h, and the final solid was ground into powder with a mortar and collected to obtain CDs. The phosphorescence performance of the prepared different CDs was then tested.

[0022] Table 1 Specific implementation scheme of Examples 1-4 Example Boric acid mass (g) Raw material molar ratio Phosphorescence intensity (au) 1 1 1:1:2 5379 2 1 1:1.5:2 8105 3 1 1:2:2 7603 4 1 1:2.5:2 7347 It can be seen from Examples 1-4 that when the precursor ratio is changed, the phosphorescence intensity of CDs shows a trend of first increasing and then decreasing, and when the volume of phosphoric acid is 800 μL and the optimal molar ratio is 1:1.5:2, the phosphorescence intensity of CDs is the strongest and the luminescence performance is the best.

[0023] The preparation process is basically the same, the only difference is that the reaction temperature in step 2) is changed.

[0024] 1) Take 1.3936 g of arginine, 800 μL of phosphoric acid and 1 g of boric acid (molar ratio of 1:1.5:2) and add them to a beaker containing 20 mL of ultrapure water. Stir the solution with a magnetic stirrer until it becomes clear. 2) The mixed solution prepared in step 1) was transferred into a polytetrafluoroethylene high-pressure reactor, and then placed in a muffle furnace, and heated at different reaction temperatures as shown in Table 2 for 8 h; 3) The brown-yellow liquid obtained by the reaction in step 2) was taken out, filtered with a 0.22 μm filter membrane to remove carbon residue, and then the brown-yellow transparent solution was transferred to a glass petri dish, placed in an oven at 180°C for 6 h, and the final solid was ground into powder with a mortar and collected to obtain CDs. The phosphorescence performance of the prepared different CDs was then tested.

[0025] Table 2 Specific implementation plan of Examples 5-8 Example Reaction temperature (℃) Phosphorescence intensity (au) 5 180 6790 6 200 7159 7 220 8105 8 240 6129 It can be seen from Examples 5-8 that when the reaction temperature is changed, the phosphorescence intensity of CDs shows a trend of first increasing and then decreasing, and when the reaction temperature is 220°C, the phosphorescence intensity reaches the highest and the luminescence performance is optimal.

[0026] The morphology and dispersion of the CDs prepared in this experiment were characterized by TEM. Figure 1 From the TEM image of part (a), it can be seen that the prepared CDs are spherical nanoparticles with good dispersibility. Figure 1 From the particle size distribution diagram in part (b), it can be seen that the particle size distribution of CDs is relatively uniform, and the average particle size is calculated to be 4.08 nm.

[0027] The chemical structure of CDs was analyzed by FTIR for Example 2. Figure 2 , at 3100-3550 cm -1 The broad absorption peak at 2550–3000 cm can be attributed to the stretching vibration of NH and OH. -1 The broad absorption peak at 1660 cm-1 represents the stretching vibration of CH. -1 The peak at 1450 cm -1 An absorption band was observed at 1190 cm -1 and 1140 cm -1 There are two smaller absorption peaks, 884 cm -1 The weak absorption peaks are due to the stretching vibration of P=O and PN. 812 cm -1 The small absorption peak at 950 cm -1 The strong absorption peaks at 502 cm -1 The absorption peak at 400 nm indicates the presence of phosphate in CDs. All FTIR results indicate that arginine reacts successfully with phosphoric acid and boric acid, and that the prepared CDs have abundant heteroatom functional groups on their surfaces.

[0028] The crystal structure of CDs was analyzed by XRD for Example 2. Figure 3 As shown, the emergence of a broad diffraction peak centered at 22.3° indicated that the prepared CDs were of amorphous carbon structure.

[0029] The room temperature phosphorescence lifetime of CDs was tested for Example 2. Figure 4 As shown, the average phosphorescence lifetime obtained by three-exponential fitting of the decay of CDs is 902 ms, which belongs to the RTP CDs with a longer lifetime.

[0030] The luminescence of the CDs powder was examined in Example 2. Figure 5 As shown, the invented CDs emit a green afterglow for about 12 s after the UV light is turned off.

[0031] The test results show that the RTP CDs doped with various atoms prepared by the hydrothermal method have higher phosphorescence intensity and afterglow time in terms of luminescence, which shows that the doping of nitrogen, phosphorus and boron atoms has a positive effect on the phosphorescence performance. At the same time, the hydrogen bonds and chemical bonds produced by the reaction between various substances weaken the vibration and rotation of the molecules, thereby promoting the ISC process.

[0032] In summary, the RTP CDs material prepared by heating arginine, phosphoric acid and boric acid by a one-step hydrothermal method has the performance of luminescence visible to the naked eye for up to 12 seconds. The cross-linking effect generated during the reaction provides a stable rigid environment for CDs, inhibiting non-radiative transitions, and doping with nitrogen, phosphorus and boron atoms makes intersystem crossing easier. The above reasons make the invented room temperature phosphorescent CDs have excellent luminescence properties and can be used in information encryption and anti-counterfeiting. The invention shows an environmentally friendly and simple method for preparing room temperature phosphorescent materials, which can provide new ideas for the preparation of luminescent carbon nanomaterials.

Claims

1. A green room temperature phosphorescent carbon dot and a preparation method thereof, characterized in that: The following steps are involved: 1) Take 1.3936 g of arginine, different volumes of phosphoric acid and 1 g of boron-containing substance, add them into a beaker containing 20 mL of solvent, and stir the solution with a magnetic stirrer until it becomes clear and transparent; 2) transferring the mixed solution prepared in step 1) into a polytetrafluoroethylene high-pressure reactor, and then placing it in a muffle furnace, reacting at a temperature of 180° C. to 240° C. for 6 h to 10 h, preferably at 220° C. for 8 h; 3) The brown-yellow carbon dot liquid obtained by the reaction in step 2) is taken out, filtered with a 0.22 μm filter membrane to remove the carbon residue, and then the brown-yellow transparent solution is transferred to a glass culture dish and placed in an oven at 180°C for 6 h. The final solid is ground into powder with a mortar and collected for later use.

2. The preparation method according to claim 1, characterized in that: The volumes of phosphoric acid in step 1) are 525, 800, 1050 and 1315 μL, preferably 800 μL, and the optimal molar ratio is 1:1.5:

2.

3. The preparation method according to claim 1, characterized in that: The solvent in step 1) is one of water, ethanol and N,N-dimethylformamide (DMF).

4. The preparation method according to claim 1, characterized in that: The boron-containing substance in step 1) is one of boric acid (H3BO3) and boron oxide (B2O3).

Citation Information

Patent Citations

  • Time-responsive color-changing phosphorescent carbon dot ink as well as preparation method and application thereof

    CN112500740A

  • Phosphorescent carbon dot-metal organic framework composite material as well as preparation method and application thereof

    CN114381261A

  • Sunlight-excited room-temperature phosphorescent carbon dot-alumina composite material and preparation method thereof

    CN117903795A

  • Long afterglow material, and preparation method and application thereof

    CN111154480A

  • Carbon nanodots capable of delaying fluorescence and room-temperature phosphorescence emission as well as preparation method and application of carbon nanodots

    CN114605993A